NPC photovoltaic grid-connected inverter using proportional-resonant controller - Maswood, Ali Iftekhar (2015)
Multi-megawatt photovoltaic (PV) power plants are widespread in electrical power systems because of the drastic decrease in the PV panel prices. The multi-string structure is considered for high power PV systems due to the increase in the overall energy conversion efficiency and the modularity when compared to the centralized topology. High power conversion can be achieved easily using parallel connection of several grid-tied two-level voltage-source inverters (2L-VSIs). However, this configuration complicates the control designs. Thus, this issue can be overcome by replacing these 2L-VSIs with a single high power three-level neutral point clamped inverter (3L-NPC). Moreover, the 3L-NPC inherits several attractive merits such as improved power quality with reduced total harmonic distortion (THD), increased overall efficiency as well as lower costs. In addition to that, the voltage oriented control using proportional-resonant (VOC-PR) in conjunction with the adaptive space vector modulation (ASVM) technique is proposed for the large-scaled PV system with grid-tied NPC inverter. The feasibility of the proposed control for the high power system is validated through the simulation results under various environmental conditions. Besides that, the dynamic mance of the system under the proposed VOC-PR is greatly enhanced in comparison with the conventional method using PI controller.